2023
DOI: 10.1007/s12144-022-04181-w
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors of Postpartum Depression During the COVID-19 Pandemic: A Review

Abstract: The COVID-19 (Coronavirus Disease 2019) pandemic has led to several mandatory prevention regulations, changes in healthcare services, unprecedented unemployment rates, financial stress, and emotional worries. Given the increasing cases of COVID-19, coupled with the drastic physical and psychological changes within postpartum mothers during the postpartum period, this paper aims to present an overview of the postpartum depression (PPD) among postpartum women during the COVID-19 pandemic. The postpartum period i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 70 publications
3
6
0
Order By: Relevance
“…Our findings echo other Saudi studies, as 74% of our study sample scored over 14 on the EPDS [13,17]. This could be due to the circumstances of the COVID-19 pandemic, as our survey was conducted between April and November 2021 (during the height of the pandemic) and reflects the critical findings of Papworth et al (2021) who found that 90% of mothers who had recently given birth felt isolated due to the COVID-19 restrictions, as well as several other international studies that showed that women during COVID-19 were more likely to present clinically significant levels of depressive and anxiety symptoms [7,9,15,33,34].…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…Our findings echo other Saudi studies, as 74% of our study sample scored over 14 on the EPDS [13,17]. This could be due to the circumstances of the COVID-19 pandemic, as our survey was conducted between April and November 2021 (during the height of the pandemic) and reflects the critical findings of Papworth et al (2021) who found that 90% of mothers who had recently given birth felt isolated due to the COVID-19 restrictions, as well as several other international studies that showed that women during COVID-19 were more likely to present clinically significant levels of depressive and anxiety symptoms [7,9,15,33,34].…”
Section: Discussionsupporting
confidence: 72%
“…The World Health Organization (WHO) prioritizes a healthy diet, that is, nutrition, weight management, physical activity, planned pregnancy, and physical, mental, and psychosocial health for women of reproductive age [1][2][3][4][5]. (Women's health issues are complex, and collaborative efforts are required to unravel some of these complexities in order to support women through their reproductive experiences, to enhance health and well-being, and to ensure better maternal outcomes [6][7][8][9]. Postpartum depression (PPD) is a common issue among childbearing women, as up to one in seven women will experience PPD [8,10,11].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations